1/3(6x-3)=-x+10+3x

Simple and best practice solution for 1/3(6x-3)=-x+10+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/3(6x-3)=-x+10+3x equation:



1/3(6x-3)=-x+10+3x
We move all terms to the left:
1/3(6x-3)-(-x+10+3x)=0
Domain of the equation: 3(6x-3)!=0
x∈R
We add all the numbers together, and all the variables
1/3(6x-3)-(2x+10)=0
We get rid of parentheses
1/3(6x-3)-2x-10=0
We multiply all the terms by the denominator
-2x*3(6x-3)-10*3(6x-3)+1=0
Wy multiply elements
-6x^2(6-30x(6+1=0

You can always share this solution

See similar equations:

| x/2+30=60 | | x/(x+1)=(x+6)/(x+1)-8/x | | 3x^2-42=105 | | 3u+7???u=0u=-74/5 | | 5x+2-6=-3x | | 9(2x-1)=7(2x | | 3(7+2m)=-15 | | 6x+16=20+180 | | 3(9+7x)=-57 | | 5x+2-6=3x | | 6x+16=20+188 | | 1x^2+5x-1=2 | | -1+7x=20 | | 2(6^2a+4)-8=48 | | 3x+6+2x+9=180 | | 2.3y=y-62 | | x=3+7/9 | | 8^b+2+4=63 | | 3x+62x+9=180 | | (y^2-y-2/5y)(10y/y+1)=2(y^2-y-2)/y+1 | | -1=21+b | | x/2+6=28 | | d+4+6=1-d | | 3.2x+9.8=1.7x+12.8 | | 3=6-3n | | 5(3-y)=20 | | x³-9x+1=0 | | 6x+14=11x-31 | | X/3x=8 | | 2^3m+3=16^2m-3 |

Equations solver categories